CAZRI Anjan 2178: A high fodder yielding Anjan grass variety for Rajasthan - Rajora, M P; Patidar, M; Sanyal, Archana (Indian Farming, 2023)
Semi-starvation of livestock is a rule in the drier parts of Rajasthan due to arid ecosystem. In fodder scarcity years, this problem worsens. However, perennial Anjan grass (Cenchrus ciliaris L.) can provide drought proofing through fodder availability, as the established pastures of this species provide nutritive fodder within two to three weeks of effective rainfall (25-30 mm). To address the issue of low animal productivity and to meet the future fodder requirement, variety CAZRI Anjan 2178 was released in 2018 from ICAR-Central Arid Zone Research Institute, Jodhpur, Rajasthan. CAZRI Anjan 2178 variety is a selection from western Rajasthan made during 1995. It is a thin stemmed variety which matures in 23-25 days (50% flowering). This variety has potential to produce 210 q per hectare green fodder and 67 q per hectare dry matter yield with an average productivity of 108 q green biomass and 38 q dry matter under rainfed conditions.